Simalungun addressing terms based on the kinship system of the Tolu Sahundulan Lima Saodoran - Purba, Ridwin; Corry, Corry; Herman, Herman; Ngongo, Magdalena; Saragih, Hisarma; Nasution, Tutiariani; Sipayung, Rohdearni Wati (Research Journal in Advanced Humanities, 2024)
Through the lens of sociolinguistics, this research looks at the dynamic between language and culture. Terms of address are also found in the Simalungun language, a local language in the Simalungun district of North Sumatera, Indonesia. Due to the kinship system of Simalungun ethnic groups, there are many different forms of addressing terms. Speakers of Simalungun must choose the correct addressing terms when speaking to the interlocutors to keep the communication going. This avoids conflict and tension at the time of commencing communication. The goal of this research is to better understand the variety of ways in which Simalungun speakers express their greetings to one another. Methodologically, this study makes use of a qualitative descriptive approach to research. The Simalungun words in current use constitute the research data. The data are collected via interviews, surveys, participant observation, a listing from the Simalungun dictionary, and recordings of Simalungun individuals speaking in a variety of settings (church, family gathering, hospital, market, meeting, party, school, university settings and workplace). The family structure of Tolu Sahundulan Lima Saodoran is the root reason of the language's extensive vocabulary of addressing terms. Personal names, kinship words, and appreciating persons are determined to be the most common forms of addressing people  in Simalungun.